Echinococcus granulosus: Cure for Cancer Revisited - Ranasinghe, Shiwanthi L.; McManus, Donald P. (Frontiers in Medicine, 2018)
Whereas a number of parasites are well recognized risk factors for a number of different cancers in mammalian hosts, there is limited information on the ability of parasitic organisms to induce anti-cancer effects. There are conflicting reports that echinococcosis, caused by the canine tapeworm Echinococcus granulosus, can decrease or increase cancer risk. This review considers both indirect anti-cancer effects as the result of adaptive immunity generated against certain echinococcal antigens and the direct effect of molecules released by E. granulosus whose activity directly inhibits cancer cell migration and growth. In conclusion E. granulosus probably secrete molecules that can develop as anti-cancer therapeutics in future.